Aspects of forming health behaviors of a child in a family - Katarzyna Wojciechowska (Kazimierz Wielki University, 2015)
Introduction. Family is the first and the natural environment which a child enters by the mere fact of appearing in the world. From that moment family house is responsible for a proper development and education of a child as well as transferring appropriate health behavior patterns. Aim. The aim of the study was to determine the connections and reliances between the quality of a family environment and children's health preferences disclosured in their behavior. It was assumed that there are many factors determining the process of health education in a family, and thus forming health-related behaviors. Material and methods. The study population consisted of a group of 126 children from kindergartens in Bydgoszcz. The empirical material was collected based on the method of diagnostic survey and observation of the health behaviors of children in various situations throughout the day in kindergarten. Results. The analysis indicated a decisive influence of factors such as parents' education, family status, economic and social conditions, participation in physical culture. They determine the quality of care for children, the amount of time spent together, the satisfaction of the biological, social and emotional needs and as a result in developing behaviors fostering or threatening the health. The practical part pinpoints the selected methods and forms of the process of health education in the family, emphasizing the role of physical activity.